Why the Fight against Poverty Is Failing: A Contrarian View - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2006)
Abraham George is the founder of The George Foundation, an NGO engaged in humanitarian work in India, and the author of India Untouched: The Forgotten Face of Rural Poverty. In this contrarian essay, he explores why the current strategies that governments and development agencies are employing to reduce poverty are not working the way they should. Among his arguments: Microcredit programs, as they are now practiced in India, do little to help the poor.